Employing soft skills in reducing organizational inertia: An exploratory analytical research in Al-Etihad Company for Food Industries Ltd in Babil Governorate - Ghazi Faisal Al-janabi, Aya; Hurajah Al -Hasnawi, Hussein (Iraqi Journal for Administrative Sciences, 2024)
The current study aimed to identify the extent to which soft skills are employed in reducing organizational inertia at the level of administrative leadership of the Etihad Company for Food Industries Ltd. in Babylon Governorate ,as soft skills were measured through six dimensions(Communication skill, teamwork skill, planning and organizing skill, leadership skills, personal mastery skill, initiative skill),while the Organizational inertia was measured through three dimensions (Insight inertia, Action inertia, psychological inertia ), In order to reach the results, the current study relied on the descriptive analytical approach in collecting, analyzing and interpreting data, and the questionnaire was used as a main tool in collecting data in a sample of (132) individuals from (Heads of departments and officials of divisions and units) The study reached a set of conclusions, the most prominent of which is the existence of a negative effect relationship with a significant significance of soft skills in organizational inertia and this indicates the possibility of investing in the skills of leaders that increase their ability to adapt to all environmental variables as well as achieving success at work and overcome difficulties.